The theory and praxis of humanitarian intervention - Tsagourias, Nikolaos K. (1996)
The aim of this thesis is to analyse the conceptual foundations of the doctrine of humanitarian intervention and scrutinise the pertinent practice within the identified lego-philosophical framework.